Dealing with the Fracture Ductile-to-Brittle Transition Zone of Ferritic Steels Containing Notches: On the Applicability of the Master Curve - Sergio Cicero; Sergio Arrieta (Metals, 2021)
Characterizing the fracture resistance of ferritic steels operating within their Ductile-to-Brittle Transition Zone (DBTZ) has been successfully addressed through the development of the well-known Master Curve (MC). This tool assumes that fracture, in the presence of crack-like defects, is controlled by weakest-link statistics and follows a three-parameter Weibull distribution. When dealing with notch-type defects, there is no standardized solution to predict the fracture resistance within the DBTZ, but the authors have published some works demonstrating that the MC can also be applied in different ways to characterize ferritic steels containing notches. One of these ways is the direct application of the MC methodology, providing a specific reference temperature (T0N) for each material and notch radius. This work reviews this initial attempt to apply the MC in notched conditions, assessing the validity of the main MC hypotheses (initially valid for cracked conditions) when analyzing notch-type defects and providing experimental validation on steels S275JR, S355J2, S460M and S690Q.